HIV seroprevalence in prisoners in Amapá - Everton Pantoja Vale; Luane da Silva Carvalho; Francis Christian da Silva Pereira (Universidade de Santa Cruz do Sul, 2016)
Backgound and Objectives: The inmates are more vulnerable to the Human Immunodeficiency Virus - HIV, resulting in a chronic and progressive disease, which can lead to destruction of the immune system and also other Sexually Transmitted Infections (STIs) due to risk factors such as sharing syringes, unprotected sex and other. The aim of this study was to monitor the prevalence of HIV circulating in the Institute of Penitentiary Administration Amapá - IAPEN in the year 2013. Methods: We analyzed 1,167 (one thousand onehundred sixty-seven) raw data of the internal IAPEN, the male and femal sexes who underwent HIV testing,they were 18 years old, during a health action undertaken by the Central Public Health Laboratory of the State of Amapá (LACEN-AP), in partnership with the Ministry of Health in 2013. Results: Through this study could noted that 18 subjects had a positive result for HIV, representing just 1.54% of th population studied and compared the analysis of the "p" risk factors did not achieve significant results> 0.05. Conclusion:Considering the importance of knowledge of this disease for the population, the results help to understand the r isk factors, their significance and to prevent the spread of HIV in the study group.